Search for invisible decays of the Higgs boson produced in association with a hadronically decaying vector boson in pp collisions at √s = 8 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2015)
A search for Higgs boson decays to invisible particles is performed using 20.3 fb−1 of pp collision data at a centre-of-mass energy of 8 TeV recorded by the ATLAS detector at the Large Hadron Collider. The process considered is Higgs boson production in association with a vector boson (V = W or Z) that decays hadronically, resulting in events with two or more jets and large missing transverse momentum. No excess of candidates is observed in the data over the background expectation. The results are used to constrain V H production followed by H decaying to invisible particles for the Higgs boson mass range 115 < mH < 300 GeV. The 95% confidence-level observed upper limit on σV H × BR(H → inv.) varies from 1.6 pb at 115 GeV to 0.13 pb at 300 GeV. Assuming Standard Model production and including the gg → H contribution as signal, the results also lead to an observed upper limit of 78% at 95% confidence level on the branching ratio of Higgs bosons decays to invisible particles at a mass of 125 GeV.